2021
DOI: 10.7759/cureus.13546
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Comorbidities in Admitting COVID-19 Pneumonia Patients in a Tertiary Care Setup: An Observational Study

Abstract: Background The novel coronavirus disease 2019 (COVID-19) is a highly infectious and pandemic disease with a variable mode of action. Patients with underlying illnesses such as diabetes, hypertension, and other diseases are more prone to infection. An understanding of the different comorbidities that place patients at the highest risk of COVID-19 pneumonia and other fatal complications associated with COVID-19 is necessary for healthcare professionals. This study aimed to determine the frequency of different co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“… 6 Another similar study done in Karachi, Pakistan showed that CKD as a comorbidity was seen in 2.83% of COVID-19 patients. 9 In A nationwide study done among 1590 hospital-admitted COVID-19 patients in China showed that 2% of patients have CKD as a comorbidity. 10 In other observation studies sought from MEDLINE, Embase and the Cochrane Library, the prevalence of CKD was 5.2 %.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 Another similar study done in Karachi, Pakistan showed that CKD as a comorbidity was seen in 2.83% of COVID-19 patients. 9 In A nationwide study done among 1590 hospital-admitted COVID-19 patients in China showed that 2% of patients have CKD as a comorbidity. 10 In other observation studies sought from MEDLINE, Embase and the Cochrane Library, the prevalence of CKD was 5.2 %.…”
Section: Discussionmentioning
confidence: 99%
“…Among 584 COVID-19 patients from 15 years and above hospitalised in the department of medicine of a tertiary care centre, the prevalence of CKD was found to be 7.36% which is slightly higher in comparison to other studies, which ranges from 0.8 -6.5 %. 4,6,[9][10][11] A study done among 445 patients in Lahore, Pakistan concluded that CKD was seen in 6.5% of COVID-19 patients. 4 A study conducted in Hyderabad, India showed that 0.8 % of COVID-19 patients had CKD as a comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…In a study done in Iran, dyspnea (72%), fever 15 (61%) and cough (57%) were the most common symptoms.In our study hypertension and type-2 diabetes were two main comorbidities found in patients with severe COVID-19 pneumonia. Other studies also found hypertension and type-2 diabetes among most common comorbidity in patients with14,16 severe COVID-19 pneumonia.The findings of this study imply that quantitative CRP analysis can be useful in determining the severity of COVID-19 and may provide additional assistance for clinical treatment strategy planning. The severe COVID-19 group had a higher average CRP values 59.6 mg/l which was consistent with14,17 previous research findings.…”
mentioning
confidence: 82%
“…A comorbidity-also called an additional diagnosis-is any concomitant disorder present in addition to the disorder that is the focus of therapy [21]. Here, the focus of treatment was COVID-19 pneumonia;…”
Section: Comorbiditiesmentioning
confidence: 99%